PRISMATIC SOCIETY THEORY STUDY OF THE SOCIAL FUNCTION OF LAND RIGHTS IN INDONESIA - Samun Ismaya (Universitas Janabadra, 2022)
Studies related to interests become an interesting study in the field of legal science, because law science itself makes interest as one of the objects of its study. Broadly speaking, interests are divided into two, namely personal interests and social interests. This interest can be attached to both moving objects and fixed objects (land).Attachment of interests to fixed objects, especially land, it is not uncommon for conflicts of interest to occur because humans (people) as legal subjects, on the one hand, are guaranteed their personal / civil interests, but on the one hand, humans cannot be separated from the social life of society. This concrete conflict of interest case occurs when national development requires land owned by community members to carry out public interests. There is a tug of war between private interests and public interests which often results in land conflicts that have broad socio-economic aspects.On the basis of the conflict of interest phenomenon, it becomes an interesting study from the perspective of legal science, especially legal theory, to be able to explain the meaning and implementation of the basic principle that